Volume 1: Turbomachinery 1990
DOI: 10.1115/90-gt-130
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Behavior in Transitional Boundary Layers Over a Range of Adverse Pressure Gradients and Turbulence Levels

Abstract: Boundary layer transition has been investigated experimentally under low, moderate and high free-stream turbulence levels and varying adverse pressure gradients. Under high turbulence levels and adverse pressure gradients a pronounced subtransition was present. A strong degree of similarity in intermittency distributions was observed, for all conditions, when the Narasimha procedure for determination of transition inception was used. Effects of free-stream turbulence on the velocity profile are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For the smooth vane suction surface transition occurs in regions where the pressure gradient is very negative. At this Reynolds number the pressure gradient at the start of transition for the smooth surface is more negative than the pressure gradient data of Gostelow et al [41], which was used by Solomon et al [33] to determine the value of the spot production parameter, N. The length of transition is very sensitive to negative pressure gradients. Figure 4a shows that an abrupt smooth suction surface transition was calculated for the 8% turbulence level.…”
Section: Heat Transfer Modeling Assumptionsmentioning
confidence: 70%
See 1 more Smart Citation
“…For the smooth vane suction surface transition occurs in regions where the pressure gradient is very negative. At this Reynolds number the pressure gradient at the start of transition for the smooth surface is more negative than the pressure gradient data of Gostelow et al [41], which was used by Solomon et al [33] to determine the value of the spot production parameter, N. The length of transition is very sensitive to negative pressure gradients. Figure 4a shows that an abrupt smooth suction surface transition was calculated for the 8% turbulence level.…”
Section: Heat Transfer Modeling Assumptionsmentioning
confidence: 70%
“…The transition length would increase if N were limited to a smaller value. The data of Gostelow and Walker [42] strongly indicate that extrapolating the correlation of Gostelow et al [41] to more negative pressure gradients would overestimate the value for N. At the lower turbulence intensity, figure 4b, the start of suction surface transition is at an even more negative pressure gradient, because the critical Reynolds number for the start of transition is increased. At the lower pressure gradient the rapid increase in intermittency is appropriate.…”
Section: Heat Transfer Modeling Assumptionsmentioning
confidence: 92%
“…. Gostelow and Walker (1991) showed that the agreement is also good for adverse pressure gradient cases on flat plates. The present data indicate that the theory does not always hold when curvature effects are introduced.…”
Section: Skin Frictionmentioning
confidence: 89%
“…The results of Walker and Gostelow (1989) indicate that the shape factor, H, is close to the local equilibrium turbulent flow value at the 99% intermittency point for the zero-pressuregradient case, but it increasingly exceeds this value as the pressure gradient becomes more adverse, which suggests the possibility that the shape factor may not be settled at the 99% intermittency point. Gostelow and Walker (1991) evaluated their transitional skinfriction values by using the relationship C f = (1-F) CfIam + I'Cf,mrb. The skin-friction value at the onset of transition was determined in the near-wall region by linear extrapolation of U + = Y+ , and the skin-friction value at transition completion was obtained by using ti K/p = 0.0464(v/U^S) 0'21U" 212.…”
Section: Introductionmentioning
confidence: 99%